"Pericope Adulterae": A Most Perplexing Passage - Grabiner, Steven (Andrews University Seminary studies, 2018)
The account of the woman caught in adultery, traditionally found in John's Gospel, is full of encouragement to sinners in need of forgiveness. Nevertheless, due to its textual history, this story - referred to as the Pericope Adulterae - is considered by many scholars to be an interpolation. The textual history is one of the most intriguing of any biblical passage. This article reviews that history, examines possible reasons for the passage's inclusion or exclusion from John's Gospel, engages discussion on the issue of its canonicity, and gives suggestions for how today’s pastors might relate to the story in their preaching.